2021
DOI: 10.3390/su13179532
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressure Wheel for Regulation of Open Channel Networks and for the Energy Supply of Isolated Sites

Abstract: The Hydrostatic Pressure Wheel is an innovative solution to regulate flow discharges and waters heights in open channel networks. Indeed, they can maintain a water depth while producing energy for supplying sensors and a regulation system. To prove the feasibility of this solution, a complete model of water depth–discharge–rotational speed relationship has been elaborated. The latter takes into account the different energy losses present in the turbine. Experimental measurements achieved in IMFT laboratory all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Clearly, the download constraint in (17) regulates the outgoing flow of a node towards its neighbors. On the other hand, the upload constraint in (18) accounts for the opposite effect, namely the capacity for a node to receive an incoming water flow from its neighbors.…”
Section: Handling Of the Network Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the download constraint in (17) regulates the outgoing flow of a node towards its neighbors. On the other hand, the upload constraint in (18) accounts for the opposite effect, namely the capacity for a node to receive an incoming water flow from its neighbors.…”
Section: Handling Of the Network Constraintsmentioning
confidence: 99%
“…Contributions: For the above reasons, a novel and versatile consensus algorithm is here presented to face the water level compensation subject to flow constraints in OCNs, which in fact translate into restrictions on the state variation [17]. Related studies concerning water distribution issues over networks can be already found in [18]- [20], where power or price-based costs are minimized in order to obtain control solutions capable of ensuring optimal governance of the active elements in the underlying network.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultra-low-head and micro-head power generation machines have become research hotspots in the field of hydropower machinery, especially in some remote areas or developing countries [1,2]. A shift of focus from million-level hydropower stations to utilizing ultra-low-head, micro-head, and tailwater head power generation devices, promotes the development of water energy resources in the open channel [3].…”
Section: Introductionmentioning
confidence: 99%